Efektivitas Implementasi Program Keluarga Berencana Dalam Menekan Laju Pertumbuhan Penduduk di Kabupaten Pulau Morotai Tahun 2017-2021 (Studi Kasus Kecamatan Morotai Selatan) - Parto Sumtaki; Jamiludin Hasan; Rahma Hasan (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
The aim of the research is to determine the effectiveness of the family planning program in reducing the rate of population growth in Morotai Island Regency (case study of South Morotai District), to determine the implementation of the family planning program in reducing the rate of population growth in Morotai Island Regency (case study of South Morotai District). This research uses a descriptive method with a qualitative approach. The descriptive method is research that aims to provide an overview of a particular society or group regarding a symptom or phenomenon. The results of this research are that the family planning program in South Morotai District is quite effective in suppressing the rate of population growth, this can be seen from several indicators used to measure the effectiveness of the family planning program, namely from program targets, outreach from technical services, to analysis of the achievements of the family planning program. , Indicators in measuring the effectiveness of the policy are reflected in the program targets, in this case, couples of childbearing age (PUS), where the percentage of women's awareness is increasing, but the socialization of the program is carried out in order to provide understanding to the public about the purpose and importance of implementation. The family planning program is less effective. Judging from the objectives of implementing the family planning program, it shows that there is a decrease in fertility levels in South Morotai District. This can be seen from the last 5 (five) years of a decline in population figures in South Morotai District.